Intelligence, Human Capital and HIV/AIDS: Fresh Exploration - Oasis Kodila-Tedika; Simplice A. Asongu (African Governance and Development Institute (AGDI), 2015)
This study complements existing literature on the relationship between HIV/AIDS and human capital by introducing previously unexplored indicators as well as more robust empirical strategies. The overarching purpose is to assess whether previous findings on the relationship withstand empirical scrutiny when alternative indicators and methodologies are employed. Four main HIV/AIDS measurements are regressed on intelligence for a maximum of 195 cross-sectional averages over the past decade. The empirical evidence is based on OLS, IWLS and 2SLS. The following findings are established. First, human capital decreases HIV prevalence with the magnitude on 'Women's share of population ages 15+ living with HIV' substantially higher. This implies improving average human capital levels across communities would be more beneficial to girls above the age of 15 living with HIV. The relatively similar negative magnitudes across other dependent variables implies that increasing human capital decreases deaths from HIV/AIDS by almost the same rate as it reduces infections to the disease. Moreover, the HIV infection rate in children between the ages of 0 and 14 does not significantly change with human capital improvements. More policy implications are discussed.
Keywords: D60; I10; I20; J24; O15; 330; Health; Human capital; Intelligence